2022
DOI: 10.1097/md.0000000000029832
|View full text |Cite
|
Sign up to set email alerts
|

The clinical characteristics and outcomes of patients with pulmonary hypertension in association with hyperthyroid state: A systematic review

Abstract: Background: Pulmonary hypertension (PHTN) may occur in thyroid disorders, especially in hypothyroidism. However, there is increasing evidence of PHTN in hyperthyroidism (HTH). The etiology, clinical course, management, and factors associated with outcomes of PHTN in the setting of HTH are unascertained. This systematic review consolidates available evidence on patients with HTH who developed PHTN. Methods: We conducted a systematic review on English articles from PubMed, Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Evaluation of thyroid function in PH patients may be warranted to detect and assess coexisting thyroid disease, although it may sometimes be missed. In a systematic review that included 589 patients with PH and hyperthyroidism, the etiologies were Graves’ disease (66.7%) as shown in our case, toxic multinodular goiter (16.8%), and thyroiditis (0.8%) [ 4 ]. It is important to note that not only hyperthyroidism but also hypothyroidism can be related to PH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of thyroid function in PH patients may be warranted to detect and assess coexisting thyroid disease, although it may sometimes be missed. In a systematic review that included 589 patients with PH and hyperthyroidism, the etiologies were Graves’ disease (66.7%) as shown in our case, toxic multinodular goiter (16.8%), and thyroiditis (0.8%) [ 4 ]. It is important to note that not only hyperthyroidism but also hypothyroidism can be related to PH.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism is not fully investigated and may be multifactorial. The proposed mechanisms are the direct effects of thyroid hormones on pulmonary vascular proliferation, the chronotropic effects of hormones on the cardiovascular system, and autoimmune-mediated endothelial dysfunction [ 4 , 5 ]. An echocardiographic examination showed that female patients with hyperthyroidism, like the present case, had elevated cardiac output and pulmonary vascular resistance [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 High-output cardiac failure, dilated cardiomyopathy, right heart failure, and pulmonary hypertension are other uncommon cardiac complications of HTH. 18,19 When HTH results in these complications or when these comorbid conditions are coupled with HTH, the risk of mortality significantly increases. Patients with HTH who develop cardiac failure have a mortality rate of up to 60% higher than that of patients with euthyroidism.…”
Section: Types Of Avbmentioning
confidence: 99%
“…Thyroid hormones work as transcription factors, and both the heart and blood arteries have thyroid hormone receptors [3,4]. Changes in the gene expression of cardiovascular system components can have profound effects on the contractile apparatus and sarcoplasmic reticulum of the myocardium [1,5]. In addition, an increase or decrease in the concentration of these hormones affects the cardiovascular system's function [1,6].…”
Section: Introductionmentioning
confidence: 99%